Abortion legislation, maternal healthcare, fertility, female literacy, sanitation, violence against women and maternal deaths: a natural experiment in 32 Mexican states. Issue 2 (23rd February 2015) - Koch, Elard; Chireau, Monique; Pliego, Fernando; Stanford, Joseph; Haddad, Sebastian; Calhoun, Byron; Aracena, Paula; Bravo, Miguel; Gatica, Sebastián; Thorp, John
Abstract : Objective: To test whether there is an association between abortion legislation and maternal mortality outcomes after controlling for other factors thought to influence maternal health. Design: Population-based natural experiment. Setting and data sources: Official maternal mortality data from 32 federal states of Mexico between 2002 and 2011. Main outcomes: Maternal mortality ratio (MMR), MMR with any abortive outcome (MMRAO ) and induced abortion mortality ratio (iAMR). Independent variables: Abortion legislation grouped as less (n=18) or more permissive (n=14); constitutional amendment protecting the unborn (n=17); skilled attendance at birth; all-abortion hospitalisation ratio; low birth weight rate; contraceptive use; total fertility rates (TFR); clean water; sanitation; female literacy rate and intimate-partner violence. Main results: Over the 10-year period, states with less permissive abortion legislation exhibited lower MMR (38.3 vs 49.6; p<0.001), MMRAO (2.7 vs 3.7; p<0.001) and iAMR (0.9 vs 1.7; p<0.001) than more permissive states. Multivariate regression models estimating effect sizes (β-coefficients) for mortality outcomes showed independent associations (p values between 0.001 and 0.055) with female literacy (β=−0.061 to −1.100), skilled attendance at birth (β=−0.032 to −0.427), low birth weight (β=0.149 to 2.166), all-abortion hospitalisation ratio (β=−0.566 to −0.962), clean water (β=−0.048 to −0.730), sanitation (β=−0.052 to −0.758) and intimate-partner violence (β=0.085 to 0.755). TFR showed an inverse association with MMR (β=−14.329) and MMRAO (β=−1.750) and a direct association with iAMR (β=1.383). Altogether, these factors accounted for (R 2 ) 51–88% of the variance among states in overall mortality rates. No statistically independent effect was observed for abortion legislation, constitutional amendment or other covariates. Conclusions: Although less permissive states exhibited consistently lower maternal mortality rates, this finding was not explained by abortion legislation itself. Rather, these differences were explained by other independent factors, which appeared to have a more favourable distribution in these states.